Functional traits and phenotypic plasticity modulate species coexistence across contrasting climatic conditions - Pérez-Ramos, Ignacio M.; Matías, Luis; Gómez-Aparicio, Lorena; Godoy, Óscar (Nature communications, 2019)
Functional traits are expected to modulate plant competitive dynamics. However, how traits and their plasticity in response to contrasting environments connect with the mechanisms determining species coexistence remains poorly understood. Here, we couple field experiments under two contrasting climatic conditions to a plant population model describing competitive dynamics between 10 annual plant species in order to evaluate how 19 functional traits, covering physiological, morphological and reproductive characteristics, are associated with species’ niche and fitness differences. We find a rich diversity of univariate and multidimensional associations, which highlight the primary role of traits related to water- and light-use-efficiency for modulating the determinants of competitive outcomes. Importantly, such traits and their plasticity promote species coexistence across climatic conditions by enhancing stabilizing niche differences and by generating competitive trade-offs between species. Our study represents a significant advance showing how leading dimensions of plant function connect to the mechanisms determining the maintenance of biodiversity. The response of traits and their plasticity to different environments within plant communities is incompletely understood. Here, the authors use field experiments under two climatic conditions to describe the dynamic relationship between ten annual plant species in association with 19 functional traits.